Comparative analysis of attitudes and emotions among inmates: does mental illness matter? - Wolff, Nancy L. (Criminal justice and behavior, 2013)
This study examines the relationship between behavioral health problems and criminogenic thinking, aggression, self-control, and hopelessness, controlling for other demographic and criminal behavior characteristics among incarcerated persons. Male (n = 3,986) and female (n = 218) inmates expected to be released within 24 months from prisons affiliated with a northeastern state department of corrections completed the Criminal Sentiments Scale?Modified, Buss?Perry Aggression Questionnaire Short-Form, Brief Self-Control Scale, and Beck Hopelessness Scale. Results indicated that behavioral health variables were significantly and substantially correlated with antisocial thinking, aggression, self-control, and hopelessness. For male inmates, serious mental illness and substance abuse problems significantly increased antisocial attitudes, aggression, and hopelessness scores and decreased self-control scores. In preparing incarcerated persons with and without mental illnesses for reentry to the community, it is critical to develop and implement evidence-based interventions that respond to attitudinal and emotional risk factors that predict relapse and recidivism.